Fault Tree Analysis of Feeding Control System for Computer Numerical Control Heavy-Duty Horizontal Lathes with Multiple Common Cause Failure Groups - 米金华 李彦锋 彭卫文 杨圆鉴 黄洪钟 (Shanghai jiao tong da xue xue bao, 2016)
The lathes are basic machine tools for manufacturing cylindrical parts. In recent years, the DL-series computer numerical control （CNC） heavy-duty horizontal lathes （HDHLs） have been widely used in the transportation, energy and aviation industries. High availability of the CNC heavy-duty lathes is demanded to guarantee the efficiency and benefit of these manufacturing industries. As one of the key subsystems of the HDHLs, the feeding control system is studied in this paper on reliability modeling and reliability analysis. The fault tree analysis （FTA） method is used for reliability modelling of the feeding control system. Considering the multiple common cause failure groups （CCFGs） existing in the system, a modified beta factor parametric model is introduced to model the common cause failure （CCF） in system. The reliability of feeding control system is then obtained and the effect of CCF on the reliability of the whole system is studied as well.